Sodium sulfate crystallisation monitoring using IR Thermography - Vazquez, P.; Thomachot-Schneider, C.; Mouhoubi, K.; Bodnar, J-L.; Avdelidis, Nicolas Peter; Charles, D.; Benavente, D. (Elsevier, 2018)
In this work, the evaporation of sodium sulfate droplets with different concentrations and at different temperatures were studied using infrared thermography (IRT). IRT allows to detect the evaporation evolution, the crystal growth and for the first time, to observe in vivo the heat release related to sodium sulfate crystallisation. A detailed study revealed that dendritic Thenardite III crystals appeared at the edge of all the crystallised droplets, though they showed a fast increase of temperature related to crystallisation only when a hydrated phase crystallised also from the droplet. The observation of the heat of crystallisation is thus directly related to the supersaturation of the droplet and consequently to temperature. In addition, IRT detection is circumscribed by the location of crystallisation. The heat can be observed and measured only when the crystallisation occurs in the interface solution – air.
Keywords: Sodium sulfate; Infrared thermography; Crystallisation; Heat release; Supersaturation